Factors Determining HIMBARA Bank Resilience: The Effect of Regulation, Adaptiveness, Assets, and Speed - Abiwodo; Athor Subroto; Umanto; Nur Fatwa (Institut Bisnis dan Informatika Kesatuan, 2025)
Banks play a central role in supporting economic growth by collecting and channeling public funds while maintaining customer trust. In Indonesia, state-owned banks face continuing pressure from economic uncertainty and rapid digital change, making their resilience a critical issue for national financial stability. This study aims to identify the key factors that determine the resilience of the four major state-owned banks and to examine how company performance and risk mediate these relationships. The research used questionnaires completed by 100 senior bank officials holding positions from Assistant Vice President level and above. Data were analysed using Structural Equation Modelling with Partial Least Squares. The results show that only six of the fourteen proposed hypotheses are supported. Regulation significantly improves company performance, while larger assets and faster response speed increase risk. Response speed directly strengthens bank resilience, and both company performance and risk significantly influence resilience. Adaptability, surprisingly, has no significant effect on any of the measured outcomes. The findings highlight that strong regulation, careful asset growth, and quick response capability are the most important drivers of resilience in Indonesian state-owned banks. Managers and regulators should focus on these three areas to ensure the banks remain stable and able to support long-term economic recovery.